KONSEP DASAR KEWIRAUSAHAAN BERBASIS NILAI-NILAI ISLAM DAN IMPLIKASINYA TERHADAP MANAJEMEN PENDIDIKAN - Nico Prasetyo; Muhammad Sidiq Purnomo (Jurnal Manajemen Pendidikan, 2026)
The main objective of this study is to formulate and comprehensively analyze the basic concept of entrepreneurship based on Islamic values ​​and its implications for educational management practices. This study uses a qualitative approach with library research. Data were obtained from books, journals, and scientific documents. The analysis used content analysis through reduction, presentation, and conclusion drawing. Data validity was tested by triangulating sources to produce a conceptual study of Islamic entrepreneurship in educational management. The results of this study indicate that entrepreneurship from an Islamic perspective is not only oriented towards economic profit but also integrates spiritual, ethical, and social values ​​such as ṣidq, amanah, fathanah, and tabligh. However, their integration in Islamic education is still not optimal, resulting in the formation of entrepreneurial character that is not systematic. On the other hand, Islamic entrepreneurship-based educational management has the potential to increase institutional independence, innovation, and competitiveness. Therefore, strengthening the curriculum and educational management is necessary to produce graduates who are religious, independent, and competitive.